Factors associated with the intention to exclusively breastfeed at Siloam Lippo Cikarang Hospital - Naomi Dewanto; Sudigdo Sastroasmoro; Rulina Suradi; Theresia Santi (Paediatrica Indonesiana, 2008)
Background World Health Organization (WHO) recommendsbreastfeeding as the appropriate method of infant feeding.Predelivery intentions about breastfeeding are strong predictorsof both initiating and continuing exclusively breastfeedingthrough the post delivery period.Objective To determine the association of age, education,occupation, parity, and information got by pregnant women withthe intention to give exclusive breastfeeding at Siloam LippoCikarang Hospital.Methods Pregnant women were chosen by consecutive samplingfilled in questionnaires contained identity, knowledge, obstacles ofbreastfeeding and intentions to exclusively breastfeed. Pregnantwomen visiting Obstetrics and Gynecologic Department SiloamLippo Cikarang Hospital who were able to read and write inIndonesian were eligible for this study.Result: Most of the 200 respondents were between 20-30 years ofage (69.5%), college graduated (55.5%), working women (50.5%),multiparous (58.5%) and have already got the informationabout breastfeeding (64.5%). The commonly cited source isprinted device (40%). Knowledge about breastfeeding in generalwere good (78%), but respondents who intended to exclusivelybreastfeed were only 58.5%. Multivariate analysis showed thatthe factors significant associated with the intention to exclusivelybreastfeed were age, with OR 0.9 (95%CI 0.84;0.98, P<0.05) andinformation, with OR 0.28 (95%CI 0.143;0.56, P<O.OOl)Conclusions The significant influencing factors to the intentionsto give exclusively breastfeed are age and information.